2015
DOI: 10.1155/2015/914231
|View full text |Cite
|
Sign up to set email alerts
|

Retrograde Intrarenal Surgery versus Percutaneous Lithotripsy to Treat Renal Stones 2-3 cm in Diameter

Abstract: Objective. Retrograde intrarenal surgery (RIRS) performed using a flexible ureterorenoscope marked the beginning of a new era in urology. Today, even staghorn stones are successfully treated via RIRS. The recommended treatment for larger stones is percutaneous nephrolithotomy (PNL). However, the question of whether PNL or RIRS should be the first-line treatment option for larger stones remains controversial. In this study, we contribute to the debate by comparing the success and complication rates of PNL and R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
36
2
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(41 citation statements)
references
References 17 publications
2
36
2
1
Order By: Relevance
“…The summarized flow chart for treatment algorithm is shown in Figure 3. 166,[174][175][176][177][178][179][180][181]184,185,188,189,[191][192][193][194][195][196][197][198][199][200][201][202][203][204][205][206]. What is an algorithm for treatment of adult patients with ureteral stones?…”
Section: Commentarymentioning
confidence: 99%
“…The summarized flow chart for treatment algorithm is shown in Figure 3. 166,[174][175][176][177][178][179][180][181]184,185,188,189,[191][192][193][194][195][196][197][198][199][200][201][202][203][204][205][206]. What is an algorithm for treatment of adult patients with ureteral stones?…”
Section: Commentarymentioning
confidence: 99%
“…A more recent study including 30 patients with renal pelvic stones over 2 cm reported an SFR of 89%. Zengin et al also evaluated the outcomes of PCNL in patients having 2-3 cm renal pelvic stones and reported a success rate of 95.5% [15]. Akman et al also investigated the success rates of PCNL in patients who had renal stones 2-4 cm in diameter and reported an SFR of 91.2%, respectively [16].…”
Section: Discussionmentioning
confidence: 99%
“…RIRS can be an effective treatment alternative to PNL [19,20]. As RIRS affords a comparable success rate to PNL and causes fewer risks of complications it seems to be a promising alternative to PNL when larger stones are to be treated [21,22].…”
Section: Pcnl Which Has Been Established In the 1970smentioning
confidence: 99%